Apprehending the Criminal : The Production of Deviance in Nineteenth Century Discourse - Leps, Marie-Christine (Book collections on Project MUSE., 1992)
In this wide-ranging analysis, Marie-Christine Leps traces the production and circulation of knowledge about the criminal in nineteenth-century discourse, and shows how the delineation of deviance served to construct cultural norms. She demonstrates how the apprehension of crime and criminals was an important factor in the establishment of such key institutions as national systems of education, a cheap daily press, and various welfare measures designed to fight the spread of criminality. Leps focuses on three discursive practices: the emergence of criminology, the development of a mass-